ENHANCING AIRPORT SECURITY: EMPLOYING DIGITAL TWINS FOR INTEGRATED CYBER-PHYSICAL SYSTEMS - Sato, Hiroki; Yamamoto, Naoko (Ayden International Journal of Basic and Applied Sciences, 2024)
Airports stand as pivotal engines of the global economy, acting as gateways for people, businesses, and tourism, fostering trade, and driving economic growth. Recent studies highlight the interconnectedness of airports and regional economic prosperity, emphasizing the role of accessibility in boosting tourism and fostering interregional business collaborations. To expedite the movement of goods and facilitate trade, airports must continuously modernize and embrace emerging technologies to manage escalating passenger numbers and enhance service quality. Over the past few decades, airport operations and business models have undergone profound transformations, adapting to the rapid expansion of the aviation sector. This evolution has witnessed a surge in passenger traffic and a broadening spectrum of choices for travelers. As airlines optimize their operational strategies to match growth with efficiency, airports have evolved in parallel. This evolution has given rise to extensive hub networks and intelligent systems, collectively forging an efficient air transportation ecosystem. However, alongside these developments emerge new challenges, as the adoption of emerging technologies, while boosting efficiency, introduces vulnerabilities that expand with an airport's economic influence and strategic significance